Cardiac-specific loss of mitoNEET expression is linked with age-related heart failure - Takaaki Furihata (Nature Portfolio, 2021)
Takaaki Furihata et al. report a new mouse model with heart-specific deletion of the mitochondrial protein, mitoNEET. Their results suggest that loss of mitoNEET expression may contribute to age-associated heart failure in older adults.